Tastes in the Roman provinces: an archaeobotanical approach to socio-cultural change - Livarda, Alexandra (Routledge, 2017)
Taste is a complicated matter. Give a plate of Brussels sprouts to a heterogeneous group of people and you will receive a range of responses, from disgusting to delicious. What determines food preferences is subject to much scholarly research, which stresses the social context as an important element in the development of tastes. Conditioned by the social environment, tastes are far from static. When one is faced, for instance, with new products, the choice to partly or fully integrate them into one’s diet, or conversely to ignore or reject them, can reflect cultural or social affinities, certain preconceptions, and in the longer term, the development of human relations as well as economic and political choices.